2016
DOI: 10.1002/cctc.201600040
|View full text |Cite
|
Sign up to set email alerts
|

High‐Valent‐Cobalt‐Catalyzed C−H Functionalization Based on Concerted Metalation–Deprotonation and Single‐Electron‐Transfer Mechanisms

Abstract: C−H functionalization has been established as a powerful strategy for the commercial construction of organic molecules. This review encompasses the most recent advances in C−H activation catalyzed by earth‐abundant cobalt complexes, involving two types of fundamental reaction paths, that is, the concerted metalation–deprotonation (CMD) path associated with non‐oxidative C−H activation and the intermolecular single‐electron‐transfer (SET) path. Transformations catalyzed by high‐valent cobalt based on the two me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 280 publications
(53 citation statements)
references
References 155 publications
1
52
0
Order By: Relevance
“…Building on the above background, we have found that pivalophenone N–H imine serves as a benzonitrile surrogate for directed C–H functionalization reactions under cobalt catalysis, 19 which is reported herein. Thus, the tert -butyl N–H imine group smoothly directs cobalt-catalyzed C–H alkylation 13 and arylation 20 with the corresponding organic halides, and then readily undergoes fragmentation into a cyano group under peroxide photolysis or aerobic copper catalysis ( Scheme 2c ).…”
Section: Introductionmentioning
confidence: 66%
“…Building on the above background, we have found that pivalophenone N–H imine serves as a benzonitrile surrogate for directed C–H functionalization reactions under cobalt catalysis, 19 which is reported herein. Thus, the tert -butyl N–H imine group smoothly directs cobalt-catalyzed C–H alkylation 13 and arylation 20 with the corresponding organic halides, and then readily undergoes fragmentation into a cyano group under peroxide photolysis or aerobic copper catalysis ( Scheme 2c ).…”
Section: Introductionmentioning
confidence: 66%
“…Two different approaches coexist in the field of Co-catalyzed C–H functionalization: the low-valent approach, 22 , 23 which has been extensively studied, and the high-valent approach. 24 …”
Section: Introductionmentioning
confidence: 99%
“…Alkyl aryl ethers are ubiquitous structural motifs present in both natural and synthetic compounds, particularly in bioactive molecules targeted as pharmaceuticals (Scheme 1) [1,2]. Compared to the traditional method for carbon-oxygen bond coupling [3][4][5][6], transition metal catalyzed C-H alkoxylation with alcohols has received much attention in recent decades in terms of atom and step economy [7][8][9][10]. However, direct C-H bond alkoxylation has been mostly limited to a palladium- [11][12][13][14][15] or copper-catalyzed system [16][17][18][19][20] which are both more biological toxicity metals.…”
Section: Introductionmentioning
confidence: 99%